2016
DOI: 10.1134/s1990341316030093
|View full text |Cite
|
Sign up to set email alerts
|

Moderate-resolution holographic spectrograph

Abstract: We present a new scheme of a moderate-resolution spectrograph based on a cascade of serial holographic gratings each of which produces an individual spectrum with a resolution of about 6000 and a bandwidth of 80 nm. The gratings ensure centering of each part of the spectrum they produce so as to provide uniform coverage of the broadest possible wavelength interval. In this study we manage to simultaneously cover the 430-680 nm interval without gaps using three gratings. Efficiency of the spectrograph optical s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The lines in a spectral image can be separated by rotating the gratings in the sagittal plane. The first version of such an optical scheme was proposed by Muslimov et al (2016a), although a similar concept can be traced back to Battey et al (1995).…”
Section: Concept Of the Instrument And Optical Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The lines in a spectral image can be separated by rotating the gratings in the sagittal plane. The first version of such an optical scheme was proposed by Muslimov et al (2016a), although a similar concept can be traced back to Battey et al (1995).…”
Section: Concept Of the Instrument And Optical Designmentioning
confidence: 99%
“…For several research areas in modern astrophysics, it would be desirable to have an instrument occupying an intermediate position between the two above-mentioned groups in the resolution-throughput space. The authors had considered a possibility of building such a spectrograph on the basis of a cascade of volume-phase holographic (VPH) gratings (Muslimov et al 2016a). As explained below, such a spectrograph combines the high efficiency of VPHs with an improved spectral resolution over an extended spectral range, which becomes possible due to the registration of multiple spectral images at the same detector simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…We should emphasize that the first three steps were considered in our previous studies [6,7] and here they serve as a starting point for further optimization and modelling.…”
Section: Modelling Strategymentioning
confidence: 99%
“…On the previous stages of the researches we developed two versions of such spectrograph for the visible domain 430-680 nm [6,7]. It was demonstrated that the spectral resolution of the full-size scheme is 0.082-0.124 nm, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…If a few of such gratings are mounted one after another with proper inclination angles in both of tangential and sagittal planes, it appears to be possible to form a spectral image consisting of several lines and characterized by a relatively high dispersion and high illuminance. Two versions of such a spectrograph were considered by the authors before 2,3 .…”
Section: Introductionmentioning
confidence: 99%